Systemic inflammation associated with severe intestinal injury in extremely low gestational age newborns. (1st June 2013) - Martin, Camilia R.; Bellomy, Melissa; Allred, Elizabeth N.; Fichorova, Raina N.; Leviton, Alan
<x xml:space="preserve">Abstract</x> To define the role of systemic inflammation in infants with intestinal perforation (IP) and necrotizing enterocolitis (NEC), we measured 25 blood protein concentrations on days 1, 7 and 14 in 939 infants born before 28 weeks' gestation. On days 7 and 14, infants with NEC had elevated levels of C-reactive protein (CRP), serum amyloid A (SAA), IL-6 and IL-8. Infants with IP had elevated levels of CRP and insulin growth factor binding protein-1 on day 7 and elevated CRP, SAA, TNF-receptor-2 and matrix metalloproteinase-9 levels on day 14. A better understanding of systemic inflammation might help prevent and treat these disorders.